Challenges for prison governors and staff in implementing the Healthy Prisons Agenda in English prisons. (September 2018) - Ismail, N.; de Viggiani, N.
Abstract: Objectives: In the two decades that have passed since the World Health Organisation established the Healthy Prisons Agenda, there has been no research conducted to investigate barriers and challenges prison managerial and operational staff encounter in implementing the Agenda in the English prison context. This article debates sectoral, institutional and occupational challenges perceived to hinder effective implementation of the Agenda, based on a qualitative study involving prison governors and operational staff. Study design: Qualitative study taking a grounded theory approach. Methods: Semistructured interviews were conducted with 30 participants comprising prison governors, prison officers and external stakeholders with key strategic and operational roles across the prison estate. The interviews were analysed and coded into themes using constant comparative method. Results: The research identified a range of managerial and operational factors that impeded recognition, acceptance and successful implementation of the Healthy Prisons Agenda. These were found to be associated with scarcity of resources, low prioritisation, perceived low importance, and pressures at operational, managerial and strategic levels to adhere to standard operating procedures. Security, control and discipline tended to supersede other imperatives considered of secondary importance to the effective running of prisons. Conclusions: Sustainability of the Healthy Prisons Agenda can only be assured by raising its significance and importance across prison hierarchies and within policies and practices through which operational and strategic objectives are realised. This means achieving wholesale commitment by prisons—among staff at all levels—towards public health goals that are fundamental to a successful and effective criminal justice system. Highlights: Prison instability after resource reduction hampers the Healthy Prisons Agenda. There are conflicting views on governor discretion and operational requirements. Prison officers overplay security, but this view is often mediated by practicality. Greater resources plus better training and clarification will sustain the Agenda.